Kojima-1Lb is a mildly cold Neptune around the brightest microlensing host star - Fukui, Akihiko; Tsapras, Yiannis; Hundertmark, Markus (The astronomical journal, 2019)
We report the analysis of additional multiband photometry and spectroscopy and new adaptive optics (AO) imaging of the nearby planetary microlensing event TCP J05074264+2447555 (Kojima-1), which was discovered toward the Galactic anticenter in 2017 (Nucita et al.). We confirm the planetary nature of the light-curve anomaly around the peak while finding no additional planetary feature in this event. We also confirm the presence of apparent blending flux and the absence of significant parallax signal reported in the literature. The AO image reveals no contaminating sources, making it most likely that the blending flux comes from the lens star. The measured multiband lens flux, combined with a constraint from the microlensing model, allows us to narrow down the previously unresolved mass and distance of the lens system. We find that the primary lens is a dwarf on the K/M boundary (0.581 ± 0.033 M ⊙) located at 505 ± 47 pc, and the companion (Kojima-1Lb) is a Neptune-mass planet (20.0 ± 2.0 M ⊕) with a semimajor axis of au. This orbit is a few times smaller than those of typical microlensing planets and is comparable to the snow-line location at young ages. We calculate that the a priori detection probability of Kojima-1Lb is only ∼35%, which may imply that Neptunes are common around the snow line, as recently suggested by the transit and radial velocity techniques. The host star is the brightest among the microlensing planetary systems (K s = 13.7), offering a great opportunity to spectroscopically characterize this system, even with current facilities.